Hunting the elusive shallow n-type donor – An ab initio study of Li and N co-doped diamond. (January 2021) - Conejeros, Sergio; Othman, M. Zamir; Croot, Alex; Hart, Judy N.; O'Donnell, Kane M.; May, Paul W.; Allan, Neil L.
Abstract: We report calculated energetics (at the GGA, and at the B3LYP, HSE06 hybrid density functional levels of theory) and electronic properties (B3LYP, HSE06) of Li and N co-doped diamond containing LiN x clusters ( x = 1–4). Defect energies and structural properties at the GGA and hybrid (B3LYP, HSE06) levels of theory are very similar. Our results for isolated Li and N dopants agree with previous work in that they are not suitable candidates for shallow n-type donors. Here, we investigate the effects of addition of N atoms as a co-dopant with Li, which vary with the Li:N ratio and whether Li is interstitial or substitutional. Reaction energies, geometries, bonding and densities of states (DOS) are examined. Nitrogen stabilises substitutional rather than interstitial lithium. Atom-projected DOS show that the chief contributions to the defect states are not from orbitals on the dopant atoms themselves but from states associated with neighbouring carbon atoms. Only the tetrahedral 1:4 cluster, LiC N4, with substitutional Li is likely to behave as a shallow donor. We propose a non-molecular synthetic route for preparation of the LiC N4 -doped material via prior generation of the N4 V centre at temperatures at which Li is mobile but LiC N4 clusters are not. Graphical abstract: Image 1